Exploring Placentophagy in Humans: Problems and Recommendations. (July 2015) - Marraccini, Marisa E.; Gorman, Kathleen S.
<x xml:space="preserve">Abstract</x> Placentophagy, the practice of afterbirth ingestion among humans, has grown among middle‐class, white women in Western societies. Although the reasons for placentophagy are varied, it is generally promoted as a means to help postpartum women stabilize mood, enhance recovery, and increase milk production. Virtually no studies have explored the effects of placentophagy on humans, and several researchers have called for studies examining the effects of human placentophagy. However, prior to examining the effects of placentophagy, a number of methodological issues need to be addressed. The present review explores research examining the effects of placentophagy in animals and humans and presents the theoretical assumptions behind placentophagy and its effects. Methodological issues related to placentophagy research are clarified, and existing research related to the nutritional and hormonal components of the placenta and their effects on milk production and postpartum depression are reviewed. Finally, implications and recommendations for future research are discussed.